2017
DOI: 10.5812/ijcm.8227
|View full text |Cite
|
Sign up to set email alerts
|

Opium Use and Risk of Lower Gastrointestinal Cancers: Population-Based Case-Control Study in South of Iran

Abstract: Background: Colorectal cancers, including colon, rectum and anus, are relatively prevalent in Iran. Use of opium and its derivatives is also considerably prevalent in some areas in Iran. Objectives: The aim of this study was to assess the association between use of opium and its derivatives, and incidence of lower gastrointestinal (LGI) cancers. Methods: This study was a matched case-control study in Shiraz (south of Iran). Cases were the new colorectal cancers from cancer registry center of Shiraz University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 35 publications
5
23
1
Order By: Relevance
“…In this study, participants with a cumulative use of ≤87.5 gram-years opium had an adjusted OR of 3.95, but participants with >87.5 gram-years had an adjusted OR of 4.79. The doseresponse relation was also observed in a previous study about O&D and LC (9); and in a study on colorectal cancer patients, in which the OR was higher in high (OR = 7.7; 95% CI: 1.5 -38.6) compared to low (OR = 3.4; 95% CI: 1.2 -9.2) opium users (20). Other studies have shown similar dose response relations between opium use and esophageal squamous cell carcinoma (4) and bladder cancer (18).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, participants with a cumulative use of ≤87.5 gram-years opium had an adjusted OR of 3.95, but participants with >87.5 gram-years had an adjusted OR of 4.79. The doseresponse relation was also observed in a previous study about O&D and LC (9); and in a study on colorectal cancer patients, in which the OR was higher in high (OR = 7.7; 95% CI: 1.5 -38.6) compared to low (OR = 3.4; 95% CI: 1.2 -9.2) opium users (20). Other studies have shown similar dose response relations between opium use and esophageal squamous cell carcinoma (4) and bladder cancer (18).…”
Section: Discussionsupporting
confidence: 79%
“…Studies dated back to the 1970s have reported the carcinogenic effects of opium; and its relation with cancers such as esophagus (3,4), stomach (5,6) larynx (7), lung (8)(9)(10) bladder (11)(12)(13)(14)(15)(16)(17)(18), colorectal (19,20) and head and neck cancers (21). Experimental studies have shown that this carcinogenic effect may be attributed to nitrogen-containing heterocyclic compounds derived from the pyrolysis of morphine (22).…”
Section: Introductionmentioning
confidence: 99%
“…The first part of the questionnaire consisted of demographic information including gender, age, education, and marital status; and the second part asked about the use of O&D, alcohol, cigarette smoking, and diet. The validity and reliability of this questionnaire had been approved in a previous study (15) and this questionnaire was used in similar studies (15,17,18).…”
Section: Tools and Methods Of Data Collectionmentioning
confidence: 99%
“…Recent studies have shown that opium and its derivatives (O&D) are a risk factor for many malignant diseases, including lung (14), gastric (15), esophageal (16), colorectal (17,18), pancreatic (19), bladder (20) and laryngeal cancer (21).…”
mentioning
confidence: 99%
“…Studies dated back to the 1970s have reported the carcinogenic effects of opium; and its relation with cancers such as esophagus (3,4), stomach (5,6) larynx (7), lung (8)(9)(10) bladder (11)(12)(13)(14)(15)(16)(17)(18), colorectal (19,20) and head and neck cancers (21). Experimental studies have shown that this carcinogenic effect may be attributed to nitrogen-containing heterocyclic compounds derived from the pyrolysis of morphine (22).…”
Section: Introductionmentioning
confidence: 99%